1993
DOI: 10.1128/mcb.13.12.7278-7287.1993
|View full text |Cite
|
Sign up to set email alerts
|

Binding of the Src SH2 Domain to Phosphopeptides is Determined by Residues in both the SH2 Domain and the Phosphopeptides

Abstract: Src homology 2 (SH2) domains are found in a variety of signaling proteins and bind phosphotyrosine-containing peptide sequences. To explore the binding properties of the SH2 domain of the Src protein kinase, we used immobilized phosphopeptides to bind purified glutathione S-transferase-Src SH2 fusion proteins. With this assay, as well as a free-peptide competition assay, we have estimated the affinities of the Src SH2 domain for various phosphopeptides relative to a Src SH2-phosphopeptide interaction whose Kd … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…These results also suggest that pY628 may be the in vivo binding site on the IL-3 receptor for SH-PTP1, although additional site(s) on the receptor may also be important for high-affinity association. One point worth mentioning is that the above Ko values are 1-3 orders of magnitude higher than those reported for pY peptides binding to other SH2 domains, such as those of Src (Payne et al, 1993;Bibbins et al, 1993), Lck (Payne et al, 1993), PI3 kinase (Felder et al, 1993), and SH-PTP2 (Sugimoto et al, 1994). We believe that pY peptides with higher affinity to SH-PTP1 SH2 domains might yet be discovered.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…These results also suggest that pY628 may be the in vivo binding site on the IL-3 receptor for SH-PTP1, although additional site(s) on the receptor may also be important for high-affinity association. One point worth mentioning is that the above Ko values are 1-3 orders of magnitude higher than those reported for pY peptides binding to other SH2 domains, such as those of Src (Payne et al, 1993;Bibbins et al, 1993), Lck (Payne et al, 1993), PI3 kinase (Felder et al, 1993), and SH-PTP2 (Sugimoto et al, 1994). We believe that pY peptides with higher affinity to SH-PTP1 SH2 domains might yet be discovered.…”
Section: Discussionmentioning
confidence: 67%
“…Further experimentation is necessary to understand this phenomenon. Bibbins et al (1993) have previously reported that a R175L mutant of Src SH2 domain is still capable of high-affinity binding to a PDGFR pY751 peptide.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphotyrosine-dependent (Yu et al, 1991;Fantl et al, 1992;Kashishian et al, 1992) and -independent binding of SH2 domains has previously been demonstrated (Cooper & Kashishian, 1993;Pendergast et al, 1991). Recently, the wild-type Src SH2 domain was shown to bind a 13-residue peptide from the /3-PDGFR KI domain incorporating Y751 (PD 751) (Bibbins et al, 1993). Further, the mutant R175L SH2 domain displayed higher affinity for this nonphosphorylated peptide than other phosphopeptides (Bibbins et al, 1993).…”
Section: Discussionmentioning
confidence: 86%
“…Recently, the wild-type Src SH2 domain was shown to bind a 13-residue peptide from the /3-PDGFR KI domain incorporating Y751 (PD 751) (Bibbins et al, 1993). Further, the mutant R175L SH2 domain displayed higher affinity for this nonphosphorylated peptide than other phosphopeptides (Bibbins et al, 1993). We are also able to show that the nonphosphorylated KI domain is able to associate with the p85 N-SH2 domain in the absence of calcium and this effect is markedly enhanced in the presence of calcium ions (Mahadevan et al, unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…The relative importance of different amino acids at a given position was determined by replacing the Z with a defined residue. The LCK SH2 domain showed a strong preference for aliphatic/hydrophobic residues (e.g., Val and Ile) at positions pY+3 and pY+4, but no apparent selectivity for N-terminal residues 54,55 (Figure 5A). This result is in accordance with the reported specificity of the LCK SH2 domain.…”
Section: Biochemistrymentioning
confidence: 99%